Involvement of the digital cushion and the distal phalanx in the development and reoccurrence of claw horn disruption lesions in dairy cattle - Newsome, Reuben F (2017)
Claw horn disruption lesions (CHDLs: sole haemorrhage, sole ulcer and white line disease) cause a large proportion of lameness in dairy cattle and have a high rate of recurrence, yet their aetiopathogenesis remains poorly understood. Untreated CHDLs appear to be associated with trauma within and damage to the internal anatomy of the foot. Chapter 2 explored associations between abnormal bone modelling on the flexor tuberosity of the distal phalanx of cull cows and lameness during life, using a retrospective cohort study design. The hind claws of 72 Holstein dairy cows culled from a research herd were imaged using μ-computed tomography (CT) and lameness and lesion incidence data were available on cows throughout life. Four measures of bone modelling were taken from CT images from the flexor tuberosity of each distal phalanx, in plantar, distal and dorsal planes, and combined within claw. Bone modelling was greater in older cows, in cows with history of CHDL and in cows that had been lame at an increased proportion of locomotion scores during the 12 months preceding slaughter. Further, histological study demonstrated that the bone modelling resembled heterotopic ossification, also termed osteoma, which could have been due to either inappropriate force transfer through the distal phalanx or pathology in the soft tissues with lesion presence. Anatomical damage within the foot does appear to be associated with lameness and CHDLs, and may further predispose lameness.